Biological-maturity status as talent-selection criterion and risk factor in alpine ski racing: A narrative review - Müller, L.; Hildebrandt, C.; Müller, E.; Raschner, C. (Science and Skiing VII, 2018)
The biological-maturity status represents an influential factor of talent selection processes and Injuries in youth ski racing. Late-maturing athletes are discriminated against in this sport; they do not have the same opportunities to reach the elite level despite their talent and efforts (Müller et al., 2016a; Müllerei al., 2016b; Müller et al., 2017a). Additionally, the biological-maturity status was revealed to be an injury risk factor among youth ski racers. Late-maturing athletes are at a higher injury risk for both traumatic and overuse injuries (Muller et al., 2017b; Müller et al., 2017c). As a consequence, the biological-maturity status has to be considered in the talent-development system in youth ski racing in order to not discriminate against late-maturing athletes in the selection process and to prevent late-maturing athletes from injuries. Both strategies should contribute to a fairer talent-development system in order to prevent high drop-out rates from occurring and to make better use of the existing talent pool in alpine ski racing in Austria. The method of calculating the APHV of the athletes seems to be a valid, easy, and feasible tool for coaches to be able to consider the biological-maturity status in the talent-development system (Müller et al., 2015a).